Mandibular Ameloblastoma in a 28-Year-Old Woman - Muhammad Apri Rajab; Widyanti Soewoto (Jurnal Kesehatan dan Kedokteran, 2025)
Ameloblastoma is a benign odontogenic tumor originating from enamel-producing epithelial cells, which, despite being benign, can grow aggressively and cause damage to surrounding structures. This case reports a 28-year-old female patient who complained of a lump on the left chin that had developed over the past three years. The lump was hard, painless, and not accompanied by systemic symptoms such as fever or weight loss. Based on clinical and supporting examinations, including MSCT and biopsy, the diagnosis of bilateral mandibular and maxillary ameloblastoma was confirmed. This tumor displayed characteristics of bone destruction and invasion into surrounding tissues, requiring radical treatment. A hemimandibulectomy procedure was chosen as the primary therapy to remove the part of the jaw infected by the tumor, with the aim of reducing the high risk of recurrence. Reconstruction with a mandibular plate was performed to restore chewing function and the patient's facial aesthetic appearance. Long-term monitoring with radiography is required to detect recurrence. Although benign, ameloblastoma can be highly destructive and requires proper treatment to prevent further damage or tumor recurrence